Morphology and thermal behaviour of SAN/EPDM blends (eXPRESS Polymer Letters)
Blends of styrene-acrylonitrile (SAN) with ethylene-propylene-diene (EPDM) with and without high impact polystyrene (HIPS) as a compatibilizer were studied. One series of blends was prepared in composition 95/5, 90/10, 85/15, 80/20 and 60/40; and the second series of blends was prepared with addition of 5 wt % of HIPS. Their morphology and thermal behaviour were inspected by scanning electronic microscopy (SEM) and dynamic mechanic analysis (DMA), respectively. Further on, blends were separated to their components by Soxlet extraction in selective solvent and characterized by Fourier Transform Infrared Spectroscopy (FTIR) and gel permeation chromatography (GPC), respectively. The results of morphological observations revealed that the addition of a small percentage of compatibilizer decreases the domain size of the dispersed phase and the compatibility of the blends was enhanced. The shifts of values of glass temperatures (Tg) in the examined blends also indicate that with addition of compatibilizer HIPS miscibility between SAN and EPDM is improved.